1 Goldline 5 years on: how a 24/7 support and coordination hub has helped to drive identification, reduce inequalities, increase use of EPaCCS and improve care for patients and their carers at the end of life. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Wilson, Linda; Livingstone, Helen
Abstract : Background: Goldline provides a 24/7 single point of contact for patients and their carers to access support, help, advice and onward referral to services. Provided by a team of generalist nurses from a DGH who access the patient's full electronic record including EPaCCS template. It is available regardless of diagnosis or identified needs to a population of 584 500 across 3 CCGs. Methods: Evaluation of service by data analysis, feedback and audit. Results: Year ending 31.3.18: 3060 patients referred, 62% ≥80 years 2368 patients died with Goldline support (47% all deaths) 14% service users died in hospital, 74% in usual place of residence, 13% hospice 74% achieved their preferred place of death 58% referrals to Gold line had a non-cancer diagnosis and 43% were not known to specialist palliative care services 38% of calls are resolved by Goldline with no onward referral 23 service concerns were received; no formal complaints/serious incidents Many compliments and messages of thanks from grateful families The service is rated highly by other professionals. Conclusions: Goldline is safely supporting patients, including those with non-cancer and not known to specialist services. 14% patients died in hospital, Airedale hospital has the lowest% patients dying in hospital in England. Goldline sits within an EOL program with many services working together to support patients and carers in their preferred place. Support in the form of education, training, coaching and facilitation provided by specialists in palliative care, EOL facilitators and GP End of Life leads across primary and secondary care has been, and will continue to be, key to enabling more patients and carers to access Goldline.